Facile synthesis and electrochemical properties of carbon-coated ZnO nanotubes for high-rate lithium storage. Issue 15 (15th October 2018) - Kim, Han-Seul; Seo, Hyungeun; Kim, Kyungbae; Lee, Jaegab; Kim, Jae-Hun
Abstract: ZnO is an important functional material, and a nanotube structure is beneficial for various applications. Here, we report the facile synthesis and electrochemical properties of carbon-coated ZnO nanotube materials as Li rechargeable battery anodes. ZnO nanorod was first synthesized via a simple hydrothermal method. Subsequently, the material was annealed with a carbon precursor, forming free-standing, carbon-coated ZnO nanotubes. The carbon-coated nanotube structure is beneficial to alleviate volume changes of the ZnO active material during Li insertion and extraction processes as well as to improve the electrochemical reaction kinetics. Electrochemical test results demonstrate that the carbon-coated ZnO nanotube electrodes deliver improved the cycling performance compared with ZnO nanorod electrodes. Better rate performance than carbon-coated ZnO nanoparticle electrodes was also achieved. Graphical abstract: fx1 Highlights: Free-standing, carbon-coated ZnO nanotubes were prepared by a facile synthetic route. Carbon-coating process was simultaneously performed with morphology transformation from nanorods to nanotubes. The carbon-coated ZnO nanotubes exhibited enhanced rate performance compared to carbon-coated ZnO nanoparticles.